1998
DOI: 10.1128/jb.180.6.1540-1548.1998
|View full text |Cite
|
Sign up to set email alerts
|

Purification of the Pyruvate Dehydrogenase Multienzyme Complex of Zymomonas mobilis and Identification and Sequence Analysis of the Corresponding Genes

Abstract: The pyruvate dehydrogenase (PDH) complex of the gram-negative bacterium Zymomonas mobilis was purified to homogeneity. From 250 g of cells, we isolated 1 mg of PDH complex with a specific activity of 12.6 U/mg of protein. Analysis of subunit composition revealed a PDH (E1) consisting of the two subunits E1α (38 kDa) and E1β (56 kDa), a dihydrolipoamide acetyltransferase (E2) of 48 kDa, and a lipoamide dehydrogenase (E3) of 50 kDa. The E2 core of the complex is arranged to form a pentagonal dodecahedron, as sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 71 publications
(38 reference statements)
4
15
2
Order By: Relevance
“…In strain ZM4 the lpd gene was mapped by hybridization more than 800 kb downstream of adhB (encoding alcohol dehydrogenase II); adhB is located close to pdhAL ( [11], embl: AF086791). This is in good agreement with our earlier results that the structural genes (pdhAK, pdhAL, pdhB and lpd) encoding the PDHC of Z. mobilis ATCC 29191 were located in two distinct chromosomal regions organized in a pdhAK-pdhAL gene cluster and a pdhB-orf2lpd gene cluster [3,7]. In this work the presence of three promoters for expression of the pdh genes of Z. mobilis is shown.…”
Section: Introductionsupporting
confidence: 93%
See 4 more Smart Citations
“…In strain ZM4 the lpd gene was mapped by hybridization more than 800 kb downstream of adhB (encoding alcohol dehydrogenase II); adhB is located close to pdhAL ( [11], embl: AF086791). This is in good agreement with our earlier results that the structural genes (pdhAK, pdhAL, pdhB and lpd) encoding the PDHC of Z. mobilis ATCC 29191 were located in two distinct chromosomal regions organized in a pdhAK-pdhAL gene cluster and a pdhB-orf2lpd gene cluster [3,7]. In this work the presence of three promoters for expression of the pdh genes of Z. mobilis is shown.…”
Section: Introductionsupporting
confidence: 93%
“…In contrast, P lpd is negatively regulated by ArcA [10]. The Z. mobilis strain ATCC 29191 used in this study has been shown to have two separate pdh gene clusters (pdhAK-pdhAL and pdhB-orf2-lpd) [3]. Previously the pdhKL region of Z. mobilis ZM4 ( [11], embl: AF086791) was sequenced and mapped, revealing more than 96% identity to the nucleotide sequence of the pdhAKL region of Z. mobilis ATCC 29191 [3].…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations